Usefulness of international evaluations for schools: teachers' perceptions as a starting point for the advice of the Education Inspection - Pérez Feijoo, Héctor Marcos (Avances en Supervisión Educativa, 2024)
Through a survey of teachers, the conclusions of a sample of scientific studies are analysed on the usefulness that the main international evaluations have on the activity carried out in educational centres, with the aim of establishing a starting point so that the Inspection of Education can carry out its collaborative function in continuous improvement. The results corroborate the statements of the scientific literature about the centrality that these evaluations occupy in the life of the centres where they are applied, the importance of the participation of teachers in the decisions of the centre, the leadership of the management teams, the key role of school libraries in skills, or the need to improve the emotional well-being of students. Although the importance of a change in the competency-based learning model is emphasized and it is recognized that the instruments used in teaching practice are not adapted, the possibility that external evaluations can support this process is rejected.
Keywords: International programs; student evaluation; competency-based education; school effectiveness; Education Inspectorate; utility of evaluations; teacher’s perceptions; counselling